2011
DOI: 10.1021/ed200234f
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of the Practices, Procedures, and Techniques in Undergraduate Organic Chemistry Teaching Laboratories

Abstract: A survey was conducted of four-year institutions that teach undergraduate organic chemistry laboratories in the United States. The data include results from over 130 schools, describes the current practices at these institutions, and discusses the statistical results such as the scale of the laboratories performed, the chemical techniques applied, the instrumentation available, the laboratory equipment used, the chemistry topics covered, the way chemical safety is presented, and how chemical waste is handled. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
51
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(52 citation statements)
references
References 0 publications
1
51
0
Order By: Relevance
“…More recently, a contributed textbook (''Green Organic Chemistry in Lecture and Laboratory'') seeks to summarize major developments made in the field during the last decade (Dicks, 2012). Surprisingly, however, a recent survey of over 130 undergraduate organic chemistry laboratories in the United States showed that although waste reduction was a significant consideration, green practical techniques were deemed relatively unimportant (Martin et al, 2011).…”
Section: Laboratory Resourcesmentioning
confidence: 99%
“…More recently, a contributed textbook (''Green Organic Chemistry in Lecture and Laboratory'') seeks to summarize major developments made in the field during the last decade (Dicks, 2012). Surprisingly, however, a recent survey of over 130 undergraduate organic chemistry laboratories in the United States showed that although waste reduction was a significant consideration, green practical techniques were deemed relatively unimportant (Martin et al, 2011).…”
Section: Laboratory Resourcesmentioning
confidence: 99%
“…School science laboratories help students build up confidence and experience before they eventually enter university laboratories. If the culture of safety in science laboratories has already been inculcated in school, students would better understand the risks inherent in university laboratories, and future accidents can be avoided (Martin et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…This was broadly in line with the techniques that most faculty expect students to learn at a similar level. 38 Experiments in the course were broken down into the practical techniques they contained. Experiments that were unreliable or did not contain the desired skills were either removed, replaced, or adapted so every experiment contained at least one skill or technique that we wanted students to learn (Table 1).…”
Section: Chemistry Coursementioning
confidence: 99%